MG-130 Utilising whole exome sequencing to identify causative variants in genetically heterogeneous disorders. (4th December 2015) - Stavropoulos, Dimitri J; Marshall, Christian R; Basran, Raveen K; Lau, Lynette; Eliou, Marianne; Orr, Jennifer; Liston, Eriskay J; Bowdin, Sarah; Meyn, MStephen; Carter, Melissa; Carew, Chris; Cohn, Ronald D; et al.
Abstract : Background: The rapid pace of innovation within the era of genomic sequencing has provided unprecedented insights into the genetic basis of human disease. Clinical whole exome sequencing provides a means for clinicians and clinical labs to take advantage of this ongoing expansion of knowledge, to benefit patient care and offer individualised medicine. Methods/results: We have developed a workflow and customised informatics pipeline suitable for processing large numbers of clinical exomes to achieve a diagnosis for genetically heterogeneous disorders. In order to guide genetic variant interpretation, we have implemented the Phenotips software tool within the hospital to collect detailed phenotype information from physicians, through a web-based interface. We describe our exome variant interpretation algorithm that integrates multiple control and clinical databases, as well as our on-site patient database to achieve a diagnosis. In order to maximise diagnostic yield, our analysis includes variants affecting all genes known to cause genetic disorders, which are prioritised according to phenotypic information provided by the referring physician. In addition, we provide patients the option of reporting secondary findings as described in the ACMG guidelines. Conclusions: This comprehensive approach provides an effective strategy for identifying causative variants in patients with genetically and phenotypically heterogeneous disorders, who would otherwise remain undiagnosed.